Sexual Violence in Ireland - Trinity FLAC; Murphy, Mary (Trinity Free Legal Advice Centre, 2018)
This research report by Trinity FLAC was conducted in association with the Rape Crisis Network. The report provides an overview of sexual violence in Ireland, taking a holistic approach that examines the societal values and political realities which surround the law as much as the law itself.
Keywords: Legal advice; Sexual violence; Rape Crisis Network; Ireland